2008
DOI: 10.1111/j.1750-3841.2008.00965.x
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Bioavailability of Nanonized Pearl Powder for Adults

Abstract: The present study was aimed to evaluate the calcium bioavailability of pearl powder for humans. Both the nanonized pearl powder (NPP) and the micronized pearl powder (MPP) prepared by a dry grinder were tested. A group of healthy adults free from hyperthyroidism, hypercalcemia, and hypocalcemia were recruited as the subjects for oral administration with the pearl powder. The bioavailability was evaluated by the serum total calcium increment, the serum intact parathyroid hormone (iPTH) reduction, and the urine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 35 publications
0
24
0
Order By: Relevance
“…Nanoemulsion delivery systems have previously been shown to improve bioavailability of nutrients such as delta-tocopherol, calcium and the vitamin-like coenzyme Q-10 molecule [14,27,28]. Pre-clinical studies have shown increased anti-cancer activity of drugs such as tamoxifen and dacarbazine, enhanced antiinflammatory property of aspirin, improved bioactivity of insulin when delivered as nanoemulsions [17][18][19]29].…”
Section: Discussionmentioning
confidence: 99%
“…Nanoemulsion delivery systems have previously been shown to improve bioavailability of nutrients such as delta-tocopherol, calcium and the vitamin-like coenzyme Q-10 molecule [14,27,28]. Pre-clinical studies have shown increased anti-cancer activity of drugs such as tamoxifen and dacarbazine, enhanced antiinflammatory property of aspirin, improved bioactivity of insulin when delivered as nanoemulsions [17][18][19]29].…”
Section: Discussionmentioning
confidence: 99%
“…The process involves milling micrometer-to nanometersized drug crystals. Nanometer-compared with micrometersized pearl powder has shown a higher bioavailability of Ca in humans as assessed by serum and urinary Ca and serum parathyroid hormone concentrations (35). In rats, supplementing the diet with nano-Ca-enriched milk was reported to increase urinary excretion of Ca (36).…”
Section: Discussionmentioning
confidence: 98%
“…(27) Nanotechnology has been reported to improve the absorption rate of drugs or nutrients due to an increase in surface area and a resulting higher solubility of the particles. (28)(29)(30) Compared with micrometer-sized pearl powder, nanometer-sized pearl powder showed a higher bioavailability of calcium in humans, as (31) Recent studies have also suggested that amorphous materials can potentially be absorbed throughout larger parts of the intestine (ie, jejunum, ileum) allowing a total higher absorption. (32) Indeed, enhanced bioavailability was demonstrated specifically for nanosized amorphous substances.…”
Section: Discussionmentioning
confidence: 99%